New records of the Auchenorrhyncha (Hemiptera) species in the fauna of Romania - Popa, Valentin (Acta entomologica slovenica (Ljubljana), 2002)
Records of seven species new to the Auchenorrhyncha fauna of Romania are presented: Stenocranus major Kbm., Alebra neglecta Wagn., Strogyllocephalus livens Zett., Colobotettix morbillosus Mel., Mendrausus pauxillus Fieb., Rhoananus hypochlorus Fieb. and Mocydiopsis longicauda Remane. The genera Colobotettix Rib., Mendrausus Rib. and Rhoananus Dlab. are new to the Romanian fauna.
Keywords: favna; Hemiptera; Romania; Romunija; škržati